Audit quality and earnings management: Evidence from China - Guo, Meiling (2017)
This paper examines the effects of ownership types and audit quality on earnings management in China and also investigates how ownership types affect the role of audit quality on earnings management. However, the prior literature focuses on the research period before 2009 and shows mixed findings. Considering the more concentrated audit market, fully convergence of IFRS, and the post share-split reform after 2009, this paper explores the differences in these research from 2010 to 2015 and predicts a more active role of high audit quality on constraining earnings manipulation while the less difference in earnings management between state-owned enterprises (SOEs) and non-state-owned enterprises (NSOEs) reduces the divergence in the effect of audit quality on these two groups. The earnings management is captured by unsigned abnormal accruals through the modified Jones model and audit quality is measured by Big 8 in China. The results prove the high audit quality and SOEs mitigate earnings management while there is no difference in the role of high audit quality on earnings management for SOEs and NSOEs.